360 제품 사진의 특성과 내적혁신성이 지속이용의도에 미치는 영향에 관한 연구 - 심현준(Hyun-Jun Sim); 이종윤(Jong-Yoon Lee); 김헌(Hun Kim) (한국콘텐츠학회 논문지, 20(6), 2020)
360 product photography is one of the realistic media technologies that can observe subjects from various angles as one of the real-world VR production methods. This study examined the effect of 360 product photography on the intention to Continuous Use through the technology acceptance model. The results of the online survey showed that informative, which is the characteristic of 360 product photography, affects both ease of use and perceived usefulness, while reliability and entertainingness affect only perceived usefulness. Internal innovation had an impact on perceived ease, but not on perceived usability. Ease of use, both mediators, had a positive effect on sustained use intention. These findings can be used as a reference for various studies in the field of 360 product photography which is still insufficient. In addition, it can provide strategic implications for the production direction of 360 product photos. 360 제품 사진은 실사를 기반으로 하는 VR 제작 방식의 하나로 피사체를 다각도에서 관찰할 수 있는 실감 미디어 기술 중 하나이다. 본 연구는 기술수용모델을 통하여 360 제품 사진의 특성과 내적혁신성이 지속이용의도에 미치는 효과를 살펴보았다. 온라인 설문조사 결과, 360 제품 사진의 특성인 정보성은 지각된 용이성과 지각된 유용성에 모두 영향을 미치고 있는 반면, 신뢰성과 오락성은 지각된 유용성에만 영향을 미치고 있는 것으로 나타났다. 내적혁신성은 지각된 용이성에 영향을 미치고 있었지만 지각된 유용성에는 영향을 미치지 않았다. 매개변인인 지각된 용이성과 지각된 유용성은 모두 지속이용의도에 정적인 영향을 미치는 것으로 나타났다. 본 연구의 결과는 아직까지 미흡한 360 제품 사진 관련 분야에 다양한 연구를 위한 참고자료로 활용될 수 있을 것이다. 더불어, 360 제품 사진의 실무 제작에 전략적인 시사점을 제공할 수 있다.